Ettaka_Lyo Project Report - Hosana Cheruto Yego; Majorine Nalwoga; Ankunda Mwebembezi; Adubo Eithyne (Uganda Christian University, 2024)
Ettaka-Lyo is a groundbreaking land law application designed to bridge the gap between landowners and legal experts. By incorporating video call and chat features along with Google Map integration, Ettaka Lyo revolutionizes access to legal assistance in land-related issues. This report provides a comprehensive overview of the development process and functionalities of Ettaka Lyo, highlighting its crucial role in facilitating legal services pertaining to land matters.